Pembinaan Kesehatan Reproduksi Remaja tentang Pencegahan Pelecehan Seksual di Lingkungan Sekolah dan Bahaya Gadget Pada Remaja di SMPN 15 Pekanbaru: Pembinaan Kesehatan Reproduksi Remaja tentang Pencegahan Pelecehan Seksual di Lingkungan Sekolah dan Bahaya Gadget Pada Remaja di SMPN 15 Pekanbaru - Hanim, Busyra; Fahrizon , Ainun Hasyri; Lestari, Budi; Endang; Yulinda, Ita; Karmina; Ariani, Danny (Ruang Ide Publisher, 2025)
Adolescents are an age group vulnerable to various reproductive health issues, including sexual harassment and the negative impacts of excessive gadget use. Gadgets are one of the results of technological advances in the modern era. While their use provides various conveniences and benefits, on the other hand, they also have negative impacts. The lack of education and supervision regarding these issues in the school environment presents a challenge in creating a safe and supportive environment for adolescent growth and development. This community service aims to increase the knowledge and awareness of Junior High School 15 Pekanbaru students regarding efforts to prevent sexual harassment and the dangers of wise gadget use on adolescent reproductive and mental health. Implementation methods include interactive counselling, group discussions, and the distribution of education media. Evaluation results showed an increase in participants knowledge about the definition, types of sexual harassment, how to prevent it, and the negative impacts of gadgets. The response from the school was very positive to this activity. It is hoped that this program can be the first step in sustainable development and be implemented in other school with similar methods.